Consecuencias sociales de los incidentes viales en la ciudad de Medellín 2015 (2017)
ABSTRACT: The road incidents in Medellin occur daily, the figures that are currently handled both from the Ministry of Mobility and the studies that are addressed from the Faculty of Public Health of the University of Antioquia give an account of how they affect the citizens of all Social classes, from pedestrians, cyclists and all the means of transport that are used in the city such as private cars, public transport and especially motorcyclists. The objective of this project is to explain the social consequences that motorcycle rider incidents leave to the city of Medellin, based on the statistics of road incidents in the city by the year 2015, selected some direct actors of these, that is to say People who were involved in road incidents by this date, who agreed to be interviewed. This research is of a qualitative, descriptive level in the communication of the findings about the social consequences of the Road Incidents in Medellin by 2015. This paper describes the experiences of different actors, who from the mobility suffered and felt the consequences that leave the road incidents to each of those involved in these events. We conducted semi-structured interviews that allowed us to understand the different situations that live both them and their families. The analysis categories give an account of the impacts that these road events generate not only to each of the people involved, but also to their families, affecting in the same way the society in general that is not yet aware of the risks and consequences Which bring the IV that daily occur in our city.